EFFECT OF COVID-19 PANDEMIC ON SLEEP PATTERNS OF HEALTH PROFESSIONALS AND MEDICAL STUDENTS IN THE KURDISTAN REGION OF IRAQ - Mzury, Abdullah Faqiyazdin Ahmed (Journal of Sulaimani Medical College, 2021)
Background Quality sleep is fundamental to human wellbeing. Healthcare providers are at the frontline of dealing with patients with COVID-19 (Coronavirus disease 2019), rendering them more susceptible to sleep disturbance by different factors. Objectives To observe sleep changes and the effect of lockdown on the duration and quality of sleep of health professionals and medical students during the COVI-19 pandemic in the Kurdistan Region of Iraq. Materials and Methods This was a descriptive cross-sectional study; a self-administered questionnaire was sent to 500 health professionals and medical students online from 2nd July 2020 to 2nd September 2020. The questionnaire used was a part of a multinational study on sleep patterns in relation to the COVID-19 pandemic (International COVID-19 sleep study, ICCOS) after permission was obtained. All methods were performed in consistence with verified regulations and guidelines. Informed consent was obtained from all participants. Data were entered by Microsoft Excel Worksheet Results A total of 304 individuals had responded to the online questionnaire; 53.6% were males. The mean age (in years) was 32.84 (± SD 11.65). The average night sleep and the average 24 hours sleep increased significantly during the COVID-19 pandemic and there was a significant statistical difference in “dreaming” patterns of the study sample before and after the pandemic. Conclusion This study concludes that the quality of sleep and daytime function of participants were not impaired despite the worldwide and national stress of the COVID-19 pandemic due to the previous lifestyle of this group of population and their ability to spend more time with their families.
Keywords: COVID-19; Sleep; Lifestyle; Health Professionals; Medical Students